2022
DOI: 10.1016/s2213-2600(21)00408-2
|View full text |Cite
|
Sign up to set email alerts
|

Post-mortem lung tissue: the fossil record of the pathophysiology and immunopathology of severe COVID-19

Abstract: The lungs are the main site that is affected in severe COVID-19, and post-mortem lung tissue provides crucial insights into the pathophysiology of severe disease. From basic histology to state-of-the-art multiparameter digital pathology technologies, post-mortem lung tissue provides snapshots of tissue architecture, and resident and inflammatory cell phenotypes and composition at the time of death. Contrary to early assumptions that COVID-19 in the lungs is a uniform disease, post-mortem findings have establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 56 publications
3
27
0
3
Order By: Relevance
“…Altogether, our findings highlight the role of a Covid-induced pro-coagulative inflammatory state that seems to affect the clinical outcomes in children as well, as reported in the adult literature [ 30 ]. Recent post-mortem adult studies have clearly documented that lung disease is characterized by “microthrombi”, endothelial inflammation and platelet activation, even in the absence of classic macroscopic embolic events [ 30 ]. This condition has now been defined as “thromboinflammation” [ 31 ].…”
Section: Discussionsupporting
confidence: 74%
“…Altogether, our findings highlight the role of a Covid-induced pro-coagulative inflammatory state that seems to affect the clinical outcomes in children as well, as reported in the adult literature [ 30 ]. Recent post-mortem adult studies have clearly documented that lung disease is characterized by “microthrombi”, endothelial inflammation and platelet activation, even in the absence of classic macroscopic embolic events [ 30 ]. This condition has now been defined as “thromboinflammation” [ 31 ].…”
Section: Discussionsupporting
confidence: 74%
“…As weak parts of the alveolar membrane are destroyed, blood components such as water molecules, plasma proteins, and platelets enter the alveolar cavity, forming pulmonary edema ( 6 ) ( Figure 1A ). Many histopathological findings showed that the most frequently reported morphological feature of COVID-19 disease is diffuse alveolar damage, characterized by a variable degree of edema in the exudate phase ( 42 , 66 , 67 ). As long as reduction of alveolar volume is compensated and thrombosis can be prevented or dissolved, the trend towards severe complications can be blocked.…”
Section: Pulmonary Vulnerabilitymentioning
confidence: 99%
“…Pathology from the primary lung target organ in COVID-19 have consistently shown that viral alveolitis is accompanied by peri-capillary myeloid and lymphoid cell infiltration [ 29 , 30 ]. Pulmonary capillary, pulmonary arteriolar and pulmonary venular vessel wall inflammation has been associated with extensive and pervasive vascular luminal thrombosis[ 2 , 31 ]. Initially, it was considered that endothelial inflammation due to direct viral infection or “viral endotheliitis” accounted for the immunothrombosis [ 29 , 32 ].…”
Section: Histological Reports Of Pulmonary Vasculitis In Covid-19 And...mentioning
confidence: 99%
“…The novel highly transmissible SARS-CoV-2 virus resulted in fatal pneumonia in a subset of patients and quickly garnered great interest in the cardiovascular and rheumatology arenas, because of the prominent vascular immunopathology. The most striking pathological feature was extensive viral alveolitis but also vascular thrombosis and reports of vascular wall inflammation [ 1 , 2 ]. Compelling evidence for extrapulmonary vasculitis and vasculitis mimics also emerged during the COVID-19 pandemic which are described in in this article.…”
Section: Introduction- the Scope Of Sars-cov-2 Related Vascular Patho...mentioning
confidence: 99%